Resonances of HCO computed using an approach based on the multiconfiguration time-dependent hartree method - Ndengué, Steve; Meyer, Hans-Dieter (The journal of physical chemistry. A, Molecules, clusters, and aerosols, 2015)
The improved relaxation method with a complex absorbing potential (CAP) was used to compute resonance states of the formyl radical (HCO) using the Heidelberg multi-configuration time-dependent Hartree (MCTDH) program. To benchmark this approach, the same potential energy surface as was used in three other method development studies was used here. It was found that the MCTDH-based approach was able to accurately and efficiently compute 90 resonance states up to more than 1 eV above the dissociation limit. Extremely close agreement was obtained for energies and widths (lifetimes) calculated using MCTDH compared with those reported previously for three other CAP-based approaches that separately involved filter-diagonalization, a preconditioned complex-symmetric Lanczos algorithm, and a non-Hermitian real-arithmatic Lanczos method. The high accuracy achieved in this benchmark study supports the applicability of MCTDH to the study of resonances in larger systems in which increased dimensionality makes the efficiency of MCTDH advantageous.
Gesehen am 17.08.2020